Au / Ag coated Cu2O-4-MBA-Van multifunctional nano composite material as well as preparation method and application thereof

By developing lychee-like hollow Au/Ag nanoparticles and Au/Ag@Cu2O-4-MBA-Van nanocomposites coated with Cu2O layer, the problems of low detection sensitivity and poor antibacterial effect in the prior art were solved, and the problem of low detection sensitivity and poor antibacterial effect was achieved. High sensitivity detection and photothermal sterilization to bacteria are suitable for a variety of detection and treatment scenarios.

CN119158506APending Publication Date: 2024-12-20JILIN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411127703.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing colloidal Au nanoparticle-based LFA detection methods have low sensitivity and are difficult to detect bacteria at low concentrations. The uneven capture and binding process of SERS immunoassays affects the accuracy. Traditional antibacterial methods are highly resistant to bacteria. Difficult to effectively suppress.

Method used

Develop a lychee-like hollow Au/Ag nanoparticles and form Au/Ag@Cu2O-4-MBA-Van nanocomposite by coating the Cu2O layer and grafting vancomycin to form an Au/Ag@Cu2O-4-MBA-Van nanocomposite as a multifunctional nanolabel for multimodal LFA detection combines colorimetric, photothermal and SERS signals to achieve high sensitivity detection and photothermal sterilization of bacteria.

Benefits of technology

Multimodal detection and photothermal sterilization of bacteria are realized, detection accuracy and efficiency are improved, photothermal conversion efficiency and antibacterial effect are high, and suitable for a variety of detection and treatment scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158506A_ABST
    Figure CN119158506A_ABST
Patent Text Reader

Abstract

The invention discloses a litchi-shaped hollow Au / Ag nano particle, the nano particle comprises an Au element and an Ag element, the surface of the nano particle is rough and is in a litchi shell shape, and the interior of the nano particle is hollow. The invention also discloses an Au / Ag coated Cu2O nano composite material, an Au / Ag coated Cu2O-4-MBA-Van nano composite material, and an LFA test paper. The invention further discloses application of the litchi-shaped hollow Au / Ag nano particles, the Au / Ag-coated Cu2O nano composite material, the Au / Ag-coated Cu2O-4-MBA-Van nano composite material and LFA test paper. According to the invention, the loaded multifunctional Au / Ag-coated Cu2O-4-MBA-Van nano composite material with colorimetric / photo-thermal / Raman comprehensive performance is constructed, and the nano composite material can be used for multi-mode LFA detection of bacteria as a nano label, and also can be used for photo-thermal therapy inactivation of bacteria.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of SERS technology, and in particular to an Au / Ag@Cu2O-4-MBA-Van multifunctional nanocomposite material and a preparation method and application thereof. Background Art

[0002] The spread of foodborne pathogenic bacteria has claimed countless lives and posed a huge threat to public health worldwide. Researchers have developed a number of analytical methods for sensitive on-site detection of bacterial contamination, including LFA, SERS immunoassay, and photothermal detection. Among them, LFA is currently the most commonly used detection platform in early disease diagnosis, food safety, and environmental monitoring. However, traditional colloidal Au nanoparticle-based LFA has disadvantages such as low sensitivity and limited quantitative detection capabilities, making it difficult to detect low-concentration bacteria. Photothermal detection is a simple and practical technology, but it is not suitable for public health emergencies due to its low sensitivity and long time consumption. In comparison, SERS immunoassay has the advantages of time saving and high sensitivity. However, the complex capture and binding processes in common SERS immunosensors can lead to uneven distribution of hot spots formed by the capture probe-bacteria SERS tag complex, which in turn affects the accuracy of the SERS method. Therefore, the inherent defects of LFA, photothermal, and SERS prompted us to develop a universal detection platform suitable for a range of application scenarios.

[0003] As an emerging detection technology, multimodal LFA, which refers to the use of multifunctional nanomaterials as LFA tags to output multiple detection signals, has become a rapidly emerging research hotspot in the field of instant detection. Multimodal LFA not only retains the simple visual qualitative judgment in the qualitative mode, but also brings together multiple quantitative modes with different sensitivity levels, which can meet the different detection needs of users and further improve the overall detection accuracy. In addition, in addition to sensitive detection of bacteria, effective sterilization is also a key link in controlling the spread of foodborne pathogens. At present, due to the tenacious protective effect of biofilms on bacteria, which leads to the emergence of bacterial resistance, it is difficult for traditional antibacterial methods to achieve satisfactory results. In recent years, the inhibition of bacteria by PTT has received widespread attention. Studies have shown that excessively high temperatures can inactivate biologically active substrates such as nucleic acids and proteins in bacterial cells and biofilms, causing bacterial cells to deform or even break. Therefore, it is very necessary to explore and develop new nanotag structures with complementary detection modes (color, photothermal and SERS signal integration) and photothermal therapy modes. In addition, in terms of excitation light, near-infrared light with a wavelength of 700-1000nm has better tissue penetration than ultraviolet light or visible light.

[0004] Au nanostars with unique optical properties and high biocompatibility can meet various needs in the field of biological monitoring and treatment. Au nanostars can produce more SERS hotspots, thereby showing a wider LSPR band in the near-infrared range and improving the photothermal effect. However, the LSPR peak of Au nanostars synthesized by conventional size control is difficult to adjust to the 808nm near-infrared wavelength most commonly used in photothermal therapy, limiting its applicability in medical treatment. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a Au / Ag@Cu2O-4-MBA-Van multifunctional nanocomposite material and its preparation method and application. The present invention constructs a multifunctional Au / Ag@Cu2O-4-MBA-Van nanocomposite material loaded with colorimetric / photothermal / Raman comprehensive properties, which can be used as a nanolabel for multimodal LFA detection of bacteria.

[0006] The invention provides a lychee-shaped hollow Au / Ag nanoparticle. The nanoparticle comprises Au element and Ag element. The surface of the nanoparticle is rough and lychee-shell-shaped, and the interior of the nanoparticle is hollow.

[0007] Preferably, the particle size of the lychee-shaped hollow Au / Ag nanoparticles is 80-100 nm.

[0008] The present invention provides a method for preparing the above-mentioned litchi-shaped hollow Au / Ag nanoparticles, comprising the following steps: mixing a nano-Ag seed solution, an Au source solution, a reducing agent and a surfactant, and reacting them to obtain litchi-shaped hollow Au / Ag nanoparticles.

[0009] The above-mentioned nano-Ag seed solution can be purchased from the market, or can be prepared according to conventional methods in the art.

[0010] After the above reaction, the lychee-shaped hollow Au / Ag nanoparticles can be uniformly dispersed in water to form a colloidal solution, which can be stored in the form of a solution for later use. The solid content of the colloidal solution is preferably 0.5-5wt%; the solution can also be freeze-dried to obtain lychee-shaped hollow Au / Ag nanoparticles.

[0011] In the above preparation process, the nano-Ag seed solution and the Au source solution may be mixed first, and then the reducing agent and the surfactant may be added and mixed.

[0012] Preferably, the reducing agent is at least one of hydroquinone and hydrazine hydrate.

[0013] Preferably, the surfactant is at least one of polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate.

[0014] Preferably, the Au source is at least one of tetrachloroauric acid, tetrachloroauric acid trihydrate and tetrachloroauric acid tetrahydrate.

[0015] Preferably, the weight ratio of nano-Ag to Au element is 1:1-2.

[0016] Preferably, the weight ratio of nano-Ag, surfactant and reducing agent is 1:50-100:150.

[0017] Preferably, the reaction is carried out at room temperature for 20-40 min with stirring at a speed of 800-1000 r / min.

[0018] The present invention also proposes an Au / Ag@Cu2O nanocomposite material, comprising: litchi-shaped hollow Au / Ag nanoparticles and a Cu2O layer coated on the surface of the litchi-shaped hollow Au / Ag nanoparticles, wherein the litchi-shaped hollow Au / Ag nanoparticles are such as the above-mentioned litchi-shaped hollow Au / Ag nanoparticles.

[0019] Preferably, the thickness of the Cu2O layer is 10-30 nm.

[0020] The present invention also provides a method for preparing the Au / Ag@Cu2O nanocomposite material, comprising the following steps: mixing lychee-shaped hollow Au / Ag nanoparticles, a surfactant, a copper source, an alkaline substance and a solvent, then adding a reducing agent, reacting, and obtaining the Au / Ag@Cu2O nanocomposite material.

[0021] After the above reaction is completed, the solid and liquid are separated, and the solid can be washed with alcohol and water to obtain the Au / Ag@Cu2O nanocomposite material.

[0022] Preferably, the solvent is at least one of water and ethanol.

[0023] Preferably, the surfactant is at least one of cetyltrimethylammonium bromide and polyvinylpyrrolidone.

[0024] Preferably, the copper source is at least one of copper chloride and copper hydroxide.

[0025] Preferably, the alkaline substance is sodium hydroxide.

[0026] Preferably, the reducing agent is at least one of ascorbic acid and hydrazine hydrate.

[0027] Preferably, the usage ratio of lychee-shaped hollow Au / Ag nanoparticles to copper source is 1 mg: 1.5-2 mmol.

[0028] Preferably, the molar ratio of the copper source, the surfactant and the alkaline substance is 1:2-3:0.2-0.25.

[0029] Preferably, the molar ratio of the copper source to the reducing agent is 1:4-5.

[0030] Preferably, the reaction is carried out at room temperature for 20-40 min.

[0031] The present invention also proposes an Au / Ag@Cu2O-4-MBA-Van nanocomposite material, on the surface of the Au / Ag@Cu2O nanocomposite material, a 4-mercaptobenzoic acid layer and a vancomycin layer are grafted and coated in sequence from the inside to the outside, wherein the Au / Ag@Cu2O nanocomposite material is such as the above-mentioned Au / Ag@Cu2O nanocomposite material.

[0032] The present invention also proposes a method for preparing the Au / Ag@Cu2O-4-MBA-Van nanocomposite material, comprising the following steps: mixing a 4-mercaptobenzoic acid solution with the Au / Ag@Cu2O nanocomposite material, performing a chelating reaction, and performing solid-liquid separation to obtain an intermediate; mixing a buffer solution in which the intermediate is dispersed with an activator, performing an activation reaction, then adding vancomycin, performing a grafting reaction, and then adding a blocking agent, performing a blocking reaction, and performing solid-liquid separation to obtain the Au / Ag@Cu2O-4-MBA-Van nanocomposite material.

[0033] The Au / Ag@Cu2O-4-MBA-Van nanocomposite material can be stored in PBS buffer. The MES buffer and PBS buffer are commonly used buffers in the art and can be purchased from the market.

[0034] The above-mentioned 4-mercaptobenzoic acid can be chelated with the Au / Ag@Cu2O nanocomposite material, and then the carboxyl group in the 4-mercaptobenzoic acid is activated to make it grafted with the amino group in vancomycin, so that the 4-mercaptobenzoic acid, vancomycin and the Au / Ag@Cu2O nanocomposite material are connected to obtain the Au / Ag@Cu2O-4-MBA-Van nanocomposite material, and finally the carboxyl group is sealed. 4-Mercaptobenzoic acid is a Raman reporter molecule that can replace the Raman signal of the target object. Vancomycin can bind to bacteria and be used as a nanotag to achieve high-sensitivity detection of bacteria. It also has the effect of photothermal sterilization.

[0035] Preferably, the solvent of the 4-mercaptobenzoic acid solution is at least one of water and ethanol.

[0036] Preferably, the amount of 4-mercaptobenzoic acid and Au / Ag@Cu2O nanocomposite material used is 0.0005-0.0015 mmol:10 mg.

[0037] Preferably, the chelation reaction is carried out at room temperature for 2-4 h.

[0038] Preferably, the buffer is MES buffer with a pH of 4-6.

[0039] Preferably, the activator is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride.

[0040] Preferably, the weight ratio of the Au / Ag@Cu2O nanocomposite material to the activator is 1:0.8-1.2.

[0041] Preferably, the activation reaction is carried out at room temperature for 20-30 min.

[0042] Preferably, the weight ratio of Au / Ag@Cu2O nanocomposite material to vancomycin is 1:0.4-0.6.

[0043] Preferably, the grafting reaction is carried out at room temperature for 1.5-2.5 hours.

[0044] Preferably, the blocking agent is at least one of ethanolamine and bovine serum albumin.

[0045] Preferably, the dosage ratio of Au / Ag@Cu2O nanocomposite material to the sealing agent is 10 mg: 0.08-0.12 mL.

[0046] Preferably, the blocking reaction is carried out at room temperature for 20-40 min.

[0047] The present invention also proposes the application of the Au / Ag@Cu2O-4-MBA-Van nanocomposite material as a SERS nanotag.

[0048] The present invention also provides an LFA test paper, comprising: a sample pad, a conjugation pad, a nitrocellulose membrane, an absorption pad and a bottom plate, wherein the conjugation pad contains a SERS nano-tag;

[0049] Wherein, the SERS nanotag is at least one of the above-mentioned Au / Ag@Cu2O-4-MBA-Van nanocomposites.

[0050] LFA is short for lateral flow chromatography. LFA is a paper-based platform that can be used to detect and quantify analytes in complex mixtures. The sample is placed on the test device and the results can be displayed quickly.

[0051] LFA is analyzed with different detection strategies according to the type of target being analyzed. The two commonly used detection strategies are mainly based on the competition and sandwich principles. Competitive immunoassay is often used to detect analytes with low molecular weight or only one binding site. For example: the principle of the competitive format can be to use the specific binding of antigen and antibody, fix the Au-labeled antibody on the binding pad, and fix the macromolecule-coupled antigen to be tested on the T line (detection line) on the surface of the nitrocellulose membrane; the secondary antibody that specifically binds to the Au-labeled antibody is fixed on the C line (quality control line); the analyte will block the antibody binding site on the T line; in this case, the antibody competes with the analyte molecule or other antibodies. A positive test result shows one line, and a negative test result shows two lines.

[0052] The sandwich detection format is used to detect relatively large molecules (such as proteins) or complex structures composed of many molecules (bacteria) in the sample. For example: the principle can be to use two monoclonal antibodies against different fragments of the analyte, the monoclonal antibody specific to the analyte is sprayed on the T line of the nitrocellulose membrane as a capture reagent, and the other antibody specific to the detection antibody is sprayed on the C line of the nitrocellulose membrane to generate a control signal; when the sample extract is applied to the sample pad, the liquid migrates upward by capillary force; some analytes bind to the detection antibody, and some remain free in the solution; then, the mixture passes through the capture zone, and the unbound analytes and bound analytes bind to the capture antibody; as a result, a positive test result is displayed as two colored areas on the nitrocellulose membrane, and a negative test result is displayed as one colored area; the response of the T line is proportional to the amount of analyte in the sample.

[0053] Preferably, a detection line is provided on the nitrocellulose membrane.

[0054] Preferably, a quality control line is provided on the nitrocellulose membrane.

[0055] In the above LFA test paper, at least one detection line is arranged on the nitrocellulose membrane.

[0056] In the above LFA test paper, a quality control line is provided on the nitrocellulose membrane.

[0057] The bottom plate plays a supporting role.

[0058] In the above LFA test paper, the nitrocellulose membrane is placed on the bottom plate, the nitrocellulose membrane has two opposite ends, the conjugate pad and the absorption pad are respectively pressed on the two ends of the nitrocellulose membrane, and the sample pad is pressed on one end of the conjugate pad and the sample pad is away from the absorption pad.

[0059] The detection line is arranged on the nitrocellulose membrane close to the conjugate pad.

[0060] The quality control line is arranged on the nitrocellulose membrane close to the absorption pad.

[0061] In the above LFA test paper, a substance A that specifically recognizes bacteria, such as an aptamer, an antibody, etc., is fixed in the detection line; preferably, an aptamer that specifically recognizes bacteria is fixed in the detection line.

[0062] The quality control line is fixed with substances that specifically recognize substance A in the detection line, such as aptamer complementary sequences, secondary antibodies, etc.

[0063] Preferably, when one detection line is provided, an aptamer that specifically recognizes bacteria is fixed in the detection line, and an aptamer is fixed in the quality control line and has a complementary sequence to the aptamer in the detection line.

[0064] Preferably, when multiple test lines are provided, each test line is fixed with an aptamer that specifically recognizes one bacterium, the quality control line is fixed with the same number of aptamers as the total number of test lines, and the aptamers in the quality control line correspond one-to-one with the aptamers in the test line to form complementary sequences.

[0065] Preferably, when multiple test lines are provided, the bacterial species in each test line may be the same or different.

[0066] The typical structure diagram of LFA test paper is as follows Figure 1 shown.

[0067] The present invention also proposes the use of the above-mentioned lychee-shaped hollow Au / Ag nanoparticles, the above-mentioned Au / Ag@Cu2O nanocomposite materials, the above-mentioned Au / Ag@Cu2O-4-MBA-Van nanocomposite materials or the above-mentioned LFA test paper in SERS detection, LFA detection, photothermal detection, and photothermal sterilization.

[0068] Preferably, the method is used in SERS detection of bacteria, LFA detection of bacteria, photothermal detection of bacteria, and photothermal sterilization.

[0069] Preferably, the bacterium is at least one of Escherichia coli, Salmonella and Staphylococcus aureus.

[0070] The SERS detection of the Au / Ag@Cu2O-4-MBA-Van nanocomposite material or the LFA test paper may be ordinary SERS detection or LFA-SERS detection, the LFA detection may be LFA-colorimetric detection, and the photothermal detection may be LFA-photothermal detection.

[0071] 1. The present invention uses a suitable reducing agent (such as hydroquinone, etc.) to prepare lychee-shaped Au / Ag nanoparticles with a hollow structure. This special structure can improve its SERS intensity and photothermal activity.

[0072] 2. The present invention coated the outer surface of lychee-shaped hollow Au / Ag nanoparticles with a Cu2O shell through a typical hydrothermal method at room temperature, and further verified the synergistic effect of EM and CM by comparing the SERS enhancement effects of Au nanoparticles, Au nanostars, Au / Ag nanoparticles and Au / Ag@Cu2O hybrids on 4-MBA (4-mercaptobenzoic acid), thereby improving their SERS intensity and photothermal activity.

[0073] 3. The present invention combines 4-MBA and Van (vancomycin) with Au / Ag@Cu2O hybrids in sequence as nanolabels, and introduces them into LFA test paper for rapid capture of E. coli; a qualitative visual mode and three switchable signal modes are provided. The Au / Ag@Cu2O-4-MBA-Van nanocomposite material has a high photothermal conversion efficiency under 808nm near-infrared light irradiation, and has a significant antibacterial effect within only 5 minutes. The Au / Ag@Cu2O-4-MBA-Van nanocomposite material described in the present invention has multiple uses, which not only realizes sensitive detection of E. coli, but also realizes effective photothermal sterilization triggered by near-infrared, and has broad application prospects in the field of pathogen detection and treatment.

[0074] The present invention constructs a multifunctional Au / Ag@Cu2O-4-MBA-Van nanocomposite material loaded with LFA-colorimetric / Raman / photothermal comprehensive performance, which can be used as a nanolabel for multimodal LFA detection of bacteria. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 Schematic diagram of the structure of LFA test paper.

[0076] Among them, 1-sample pad; 2-binding pad; 3-detection line; 4-quality control line; 5-absorption pad; 6-nitrocellulose membrane; 7-SERS nano tag; 8-bottom plate.

[0077] Figure 2 These are morphology detection images of litchi-shaped hollow Au / Ag nanoparticles, where (A) is the TEM image of nano-Ag seeds, (B) is the TEM image of litchi-shaped hollow Au / Ag nanoparticles, and (C) is the high-angle annular dark field image of litchi-shaped hollow Au / Ag nanoparticles and the corresponding EDX element mapping image (Au and Ag).

[0078] Figure 3 Figure 2 shows the optical properties and SERS effect results of lychee-shaped hollow Au / Ag nanoparticles, Au nanoparticles, Au@Ag nanoparticles, and Au nanostars. (A) is a UV-Vis image, (B) is a color image, (C) is the SERS spectrum of 4-MBA adsorbed on each particle, and (D) is the SERS spectrum of 1589 cm-1 in (C). -1Spectral intensity of the peak positions, AuNPs are Au nanoparticles, Au@AgNPs are Au@Ag nanoparticles, GNS are Au nanostars, and Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles.

[0079] Figure 4 The morphology detection diagram of Au / Ag@Cu2O nanocomposites, where (A) is the TEM image, high-angle annular dark field image and corresponding EDX element mapping image (Ag, Au, Cu and O) of the Au / Ag@Cu2O nanocomposites; (B) is the XRD spectrum of the Au / Ag@Cu2O nanocomposites; (C) is the UV-Vis absorption spectrum of lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites, Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles, and Au / Ag@Cu2O is Au / Ag@Cu2O nanocomposites.

[0080] Figure 5 Figure 2 is the SERS detection result of Au / Ag@Cu2O nanocomposites, where (A) is the SERS spectrum of 4-MBA adsorbed on lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites; (B) is a schematic diagram of the structural evolution of Au / Ag@Cu2O nanocomposites; (C) is the electric field distribution diagram of lychee-shaped hollow Au / Ag nanoparticles and (D) Au / Ag@Cu2O nanocomposites, Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles, and Au / Ag@Cu2O is Au / Ag@Cu2O nanocomposites.

[0081] Figure 6 (A) is the fluorescence spectrum of Cu2O nanoparticles and Au / Ag@Cu2O nanocomposites; Figure 6 (B) Schematic diagram of the charge transfer process between Au / Ag@Cu2O nanocomposite and 4-MBA.

[0082] Figure 7The photothermal effect results of Au / Ag@Cu2O nanocomposites, where (A) is the infrared thermal image of water, Au@Ag nanoparticles, lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites after 5 minutes of 808nm laser action, and (B) is the corresponding temperature curve of (A); (C) is a schematic diagram of the scattering and absorption effects of incident light on different nanoparticles; (D) is the calculated result of the photothermal conversion efficiency of Au / Ag@Cu2O nanocomposites, Au@AgNPs are Au@Ag nanoparticles, Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles, and Au / Ag@Cu2O NPs and Au / Ag@Cu2O are both Au / Ag@Cu2O nanocomposites.

[0083] Figure 8 The results of LFA detection using Au / Ag@Cu2O-4-MBA-Van nanocomposites as nanolabels, including the colorimetric photos (A) and photothermal photos (B) of the LFA test strips of E. coli at different concentrations; (C) -8 cfu / mL) of Escherichia coli, (D) is 1589 cm -1 Logarithmic plot of SERS intensity and E. coli concentration.

[0084] Fig. 9 The plasmonic photothermal effect and cytotoxicity results of Au / Ag@Cu2O-4-MBA-Van nanocomposite as nanotag, including live and dead fluorescence images of Escherichia coli with (A) no laser treatment, (B) laser treatment only, (C) nanotag treatment only, and (D) simultaneous treatment of nanotag and near-infrared laser. DETAILED DESCRIPTION

[0085] The technical solution of the present invention is described in detail below through specific embodiments.

[0086] Example 1

[0087] A method for preparing lychee-shaped hollow Au / Ag nanoparticles comprises the following steps:

[0088] 36 mg of AgNO3 was dissolved in 200 mL of deionized water and heated to 100°C for 15 min. 4 mL of trisodium citrate dihydrate was immediately added at a slight boiling point and reacted at 85°C for 50 min until the solution color turned grayish yellow-green to obtain a nano-Ag seed solution.

[0089] It was prepared by potential difference etching, and 100 μL of an aqueous solution of tetrachloroauric acid trihydrate and 1 mL of a nano-Ag seed solution were added to 10 mL of deionized water, so that the weight ratio of nano-Ag to Au element was 1:1.5. The mixture was stirred at 400 r / min for 5 min at room temperature, and the color of the solution was observed to change from light yellow to light purple. The stirring speed was then adjusted to 800 r / min, and aqueous solutions of polyvinyl pyrrolidone and hydroquinone were added, so that the weight ratio of nano-Ag, polyvinyl pyrrolidone and hydroquinone was 1:70:150. The mixture was stirred and reacted for 30 min to obtain a lychee-shaped hollow Au / Ag nanoparticle colloidal solution with a solid content of 2 wt%. The color of the solution eventually turned into dark blue.

[0090] The lychee-shaped hollow Au / Ag nanoparticle colloidal solution prepared in Example 1 was tested and the results were as follows: Figure 2 shown. Figure 2 These are morphology detection images of litchi-shaped hollow Au / Ag nanoparticles, where (A) is the TEM image of nano-Ag seeds, (B) is the TEM image of litchi-shaped hollow Au / Ag nanoparticles, and (C) is the high-angle annular dark field image of litchi-shaped hollow Au / Ag nanoparticles and the corresponding EDX element mapping image (Au and Ag).

[0091] Depend on Figure 2 (A) It can be seen that the average diameter of the nano-Ag seeds is about 60nm.

[0092] Under the action of hydroquinone reduction and electro-substitution reaction, the metallic states of Ag and Au continuously grow on the Au / Ag complex to obtain the final product. Figure 2 (B) It can be seen that the surface of the Au / Ag nanoparticles is not smooth and presents a shape similar to that of lychee shells. The particle size ranges from 80-100nm, and the particles present a hollow structure. During the electrical substitution process, Au atoms are initially deposited on the surface of the Ag nanoparticles as electron donors for the reduction reaction. The further reduced Au atoms reside on the initial Au layer and grow epitaxially, and because the Ag seeds are oxidized and dissolved in the solution, the space occupied by the Ag atoms cannot be filled by Au atoms, resulting in the formation of a hollow interior. From Figure 2 (C) It can be seen that the hollow particles are composed of Au and Ag, and the compositions of Au and Ag are almost completely overlapped, which is equivalent to a bimetallic Au / Ag alloy. It can also be found that the Ag element is mainly distributed on the surface of the nanoparticles, while there is also a small amount of Ag element inside, indicating that the Ag seeds are not replaced by Au during the reaction. III Fully etched.

[0093] Comparative Example 1

[0094] The preparation of Au nanoparticles comprises the following steps: using chloroauric acid as a raw material, adding 10 mg of chloroauric acid into 99 mL of an aqueous solution, then reflux-heating at 105° C., adding 80 mg of trisodium citrate dihydrate after boiling and keeping the temperature at 80° C. for 10 min, cooling to room temperature in a dark environment, and obtaining an Au nanoparticle solution.

[0095] Comparative Example 2

[0096] The preparation of Au@Ag nanoparticles includes the following steps: taking 100 mL of the Au nanoparticle solution prepared in Comparative Example 1, reflux heating to boiling, adding 16 mg of silver nitrate and 40 mg of reducing agent trisodium citrate dihydrate, mixing, reacting for 50 minutes to reduce the Ag shell on the surface of the Au nanoparticles, centrifuging, washing with water, and drying to obtain Au@Ag nanoparticles.

[0097] Comparative Example 3

[0098] The preparation of Au nanostars comprises the following steps: under vigorous stirring, mixing 10 g / L of chloroauric acid aqueous solution with the Au nanoparticle solution of comparative example 1, 10 g / L of trisodium citrate dihydrate aqueous solution and 3 g / L of hydroquinone aqueous solution in a volume ratio of 1:0.5:0.2:10; finally, stirring the mixed solution at room temperature for 30 minutes, centrifuging, washing with water and drying to obtain Au nanostars.

[0099] The lychee-shaped hollow Au / Ag nanoparticles of Example 1 and the Au nanoparticles, Au@Ag nanoparticles, and Au nanostars prepared in Comparative Examples 1-3 were taken; their optical properties and SERS effects were tested in the same manner. The results are as follows: Figure 3 shown. Figure 3 Figure 2 shows the optical properties and SERS effect results of lychee-shaped hollow Au / Ag nanoparticles, Au nanoparticles, Au@Ag nanoparticles, and Au nanostars. (A) is a UV-Vis image, (B) is a color image, (C) is the SERS spectrum of 4-MBA adsorbed on each particle, and (D) is the SERS spectrum of 1589 cm-1 in (C). -1 Spectral intensity of the peak positions, AuNPs are Au nanoparticles, Au@AgNPs are Au@Ag nanoparticles, GNS are Au nanostars, and Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles.

[0100] The intrinsic absorption capacity of nanoparticles is the key to improving detection performance. Figure 3(AB) It can be seen that: Au nanoparticles have a typical LSPR peak at 520nm, and the solution color is pink; Au@Ag nanoparticles have an absorption peak at 400nm, and the solution color is orange-yellow; Au nanostars have an LSPR absorption peak at 650nm, with a wider bandwidth and an obvious red shift; lychee-shaped hollow Au / Ag nanoparticles, during the particle formation process, Au 3+ The electro-replacement reaction with Ag leads to a decrease in the internal area of ​​the nanoparticles, the LSPR peak moves toward longer wavelengths in the visible region, and the morphology of the nanoparticles changes toward a hollow structure; the lychee-shaped hollow Au / Ag nanoparticles produce an obvious longitudinal plasmon peak at 750nm, proving that the lychee-shaped hollow Au / Ag nanoparticles have near-infrared absorption. The wide absorption in the visible and near-infrared regions indicates that the lychee-shaped hollow Au / Ag nanoparticles can be used as excellent photothermal conversion agents in LFA.

[0101] Depend on Figure 3 (CD) It can be seen that: compared with Au nanoparticles and Au@Ag nanoparticles, Au nanostars show stronger SERS enhancement effect, because Au nanostars with multiple anisotropic branches can form a large number of SERS hotspots at the tip; while the lychee-shaped hollow Au / Ag nanoparticles can significantly improve the SERS activity due to the enrichment of Ag in the hollow nanostructure, generating more "hotspots" to enhance the local field, and the SERS activity reaches the maximum value. And the anisotropic cross-section, large specific surface area and rougher surface provide more adsorption space for target molecules. Therefore, the composition, shape and morphology of lychee-shaped hollow Au / Ag nanoparticles play a more important role in enhancing SERS, and have potential application prospects in molecular detection in the near-infrared region. It can be easily concluded that the best SERS performance occurs on lychee-shaped hollow Au / Ag nanoparticles.

[0102] Example 2

[0103] A method for preparing an Au / Ag@Cu2O nanocomposite material comprises the following steps:

[0104] Under stirring at room temperature, 1.5 mL of the lychee-shaped hollow Au / Ag nanoparticle colloidal solution with a solid content of 2 wt% obtained in Example 1, 1 mL of a 0.005 M hexadecyltrimethylammonium bromide aqueous solution, 200 μL of a 0.01 M CuCl2 aqueous solution, and 45 μL of a 0.01 M NaOH aqueous solution were added to 5 mL of deionized water, and then 90 μL of 0.1 M ascorbic acid was added. The mixture was stirred at room temperature for 30 min, centrifuged, and the solid was washed 3 times with alcohol and deionized water, respectively, to obtain an Au / Ag@Cu2O nanocomposite material.

[0105] The Au / Ag@Cu2O nanocomposite material prepared in Example 2 was tested and the results were as follows: Figure 4 shown. Figure 4 The morphology detection diagram of Au / Ag@Cu2O nanocomposites, where (A) is the TEM image, high-angle annular dark field image and corresponding EDX element mapping image (Ag, Au, Cu and O) of the Au / Ag@Cu2O nanocomposites; (B) is the XRD spectrum of the Au / Ag@Cu2O nanocomposites; (C) is the UV-Vis absorption spectrum of lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites, Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles, and Au / Ag@Cu2O is Au / Ag@Cu2O nanocomposites.

[0106] In the presence of surfactant and copper source, Cu2O nanoparticles grow on lychee-shaped hollow Au / Ag nanoparticles. Figure 4 (A) It can be seen that the surface of the Au / Ag@Cu2O nanocomposite is rough with high uniformity and monodispersity, and the Cu2O shell grows on the surface of the lychee-shaped hollow Au / Ag nanoparticles, where the thickness of the Cu2O shell is about 20nm; the high-angle annular dark field scanning image and elemental mapping image of the Au / Ag@Cu2O nanocomposite show the elemental composition of the nanocomposite, confirming the coexistence of Ag, Au, Cu and O; Cu and O element signals are widely detected on the entire material surface, indicating the integration of the core-shell Au / Ag-Cu2O system.

[0107] Depend on Figure 4 (B) It can be seen that the diffraction peaks observed at 2θ values ​​of 38.2°, 44.3°, 64.5° and 77.5° belong to the (111), (200), (220) and (311) crystal planes of the lychee-shaped hollow Au / Ag nanoparticles, respectively. At the same time, the peaks at 36.4°, 42.2°, 61.2° and 73.4° can be pointed to the (111), (200), (220) and (311) crystal planes of Cu2O, respectively, and no other impurities were found.

[0108] The plasmon properties of lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites were studied by UV-Vis spectroscopy. Figure 4(C) It can be seen that compared with the lychee-shaped hollow Au / Ag nanoparticles, the LSPR peak of the Au / Ag@Cu2O nanocomposite is red-shifted to a longer wavelength (940nm) and has stronger near-infrared absorption; in addition, the Au / Ag@Cu2O nanocomposite has a broadened absorption at about 450nm, which is considered to be the band gap absorption of Cu2O. The red shift and broadening of the transverse and longitudinal absorption can be attributed to the high refractive index of Cu2O (≈2.705). The LSPR of the Au / Ag@Cu2O nanocomposite in the near-infrared region enables it to convert 808nm laser light into a photothermal effect, which can penetrate deep tissues and cause less nonspecific damage to surrounding tissues and normal cells.

[0109] The lychee-shaped hollow Au / Ag nanoparticles of Example 1 and the Au / Ag@Cu2O nanocomposite prepared in Example 2 were taken; 4-MBA was used as a Raman reporter molecule, and their optical properties and SERS effects were detected in the same manner. The results are as follows: Figure 5 shown.

[0110] Figure 5 Figure 2 is the SERS detection result of Au / Ag@Cu2O nanocomposites, where (A) is the SERS spectrum of 4-MBA adsorbed on lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites; (B) is a schematic diagram of the structural evolution of Au / Ag@Cu2O nanocomposites; (C) is the electric field distribution diagram of lychee-shaped hollow Au / Ag nanoparticles and (D) Au / Ag@Cu2O nanocomposites, Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles, and Au / Ag@Cu2O is Au / Ag@Cu2O nanocomposites.

[0111] Depend on Figure 5 (A) It can be seen that the SERS signal of Au / Ag@Cu2O nanocomposite material is the strongest.

[0112] In order to explore the physical mechanism behind SERS enhancement, the electromagnetic field distribution of lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites was calculated using the finite element method. Figure 5(CD) It can be seen that electromagnetic hot spots are generated on the branch surface in the lychee-shaped hollow Au / Ag nanoparticle structure. This is due to the higher charge distribution near the branch structure, which leads to a stronger electromagnetic field distribution and better enhancement effect. For the Au / Ag@Cu2O nanocomposite, the strong electric field around the branch still exists. Interestingly, the Au / Ag@Cu2O nanocomposite produces a stronger electromagnetic field enhancement due to the additional coupling of the Cu2O shell to Au / Ag. On the one hand, high refractive index semiconductors are key to electromagnetic enhancement because they can increase the optical path length of the excitation light and improve the light capture ability. On the other hand, the larger electromagnetic field enhancement can be attributed to the vibrational coupling of various resonances in the Au / Ag@Cu2O nanocomposite, such as surface plasmon resonance, exciton resonance, and molecular resonance. This may contribute to the generation and transfer of charges between Au / Ag nanoparticles and Cu2O. This explains why the SERS signal of the Au / Ag@Cu2O nanocomposite is stronger than that of the lychee-shaped hollow Au / Ag nanoparticles.

[0113] Figure 6 (A) is the fluorescence spectrum of Cu2O nanoparticles and Au / Ag@Cu2O nanocomposites; Figure 6 (B) Schematic diagram of the charge transfer process between Au / Ag@Cu2O nanocomposite and 4-MBA.

[0114] Depend on Figure 6 (A) It can be seen that the PL intensity of Au / Ag@Cu2O nanocomposites is significantly reduced compared to Cu2O nanoparticles. This is because the interface between Au / Ag and Cu2O nanoparticles forms a Schottky barrier, which acts as an electron trap to capture photogenerated electrons, thereby effectively suppressing the recombination of photogenerated electron-hole pairs and improving the separation and transfer ability of electron-hole pairs. Therefore, Au / Ag introduces electron traps, resulting in accelerated electron transfer. These PL results are in good agreement with the SERS measurement results, so effective charge transfer in Au / Ag@Cu2O nanocomposites plays an important role in improving SERS performance.

[0115] To explain the possible CT between Au / Ag@Cu2O nanocomposites and 4-MBA molecules, Figure 6(B) The CT mechanism is proposed. The work function value of Au / Ag is about 4.50 eV, which is lower than the Fermi level of Cu2O (4.84 eV). Therefore, the charge is transferred from Au / Ag to Cu2O until the Fermi levels of the two systems are consistent. Due to the LSPR effect of the noble metal, the electrons in Au / Ag are first excited by the laser, and then the excited charges are rapidly transferred from Au / Ag to the CB state of Cu2O and / or vibrationally relax to the surface state energy level (ESS) of Cu2O, and finally transferred to the LUMO orbit of 4-MBA, which increases the probability of electron transfer to the 4-MBA molecule. The CB and ESS of Cu2O act as bridges between Au / Ag nanoparticles (donors) and probe molecules (acceptors). Therefore, both the EM enhancement mechanism and the CM enhancement mechanism contribute to amplifying the SERS activity of Au / Ag@Cu2O nanocomposites.

[0116] In order to test the photothermal effect of nanoparticles, the surface temperature changes of spherical Au@Ag nanoparticles (Comparative Example 2), lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites after 808nm laser irradiation for 5 minutes were monitored by infrared thermal imaging camera, and deionized water was used as blank control. The results are shown in Figure 2. Figure 7 shown.

[0117] Figure 7 The photothermal effect results of Au / Ag@Cu2O nanocomposites, where (A) is the infrared thermal image of water, Au@Ag nanoparticles, lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites after 5 minutes of 808nm laser action, and (B) is the corresponding temperature curve of (A); (C) is a schematic diagram of the scattering and absorption effects of incident light on different nanoparticles; (D) is the calculated result of the photothermal conversion efficiency of Au / Ag@Cu2O nanocomposites, Au@AgNPs are Au@Ag nanoparticles, Au / AgHNPs are lychee-shaped hollow Au / Ag nanoparticles, and Au / Ag@Cu2O NPs and Au / Ag@Cu2O are both Au / Ag@Cu2O nanocomposites.

[0118] Depend on Figure 7 (A) It can be seen that the temperature of the control sample water did not rise significantly, and the photothermal performance of Au@Ag nanoparticles was far inferior to that of lychee-shaped hollow Au / Ag nanoparticles; the introduction of Cu2O caused the temperature of the Au / Ag@Cu2O nanocomposite material to rise the most; the temperature of the Au / Ag@Cu2O nanocomposite solution gradually increased with the extension of irradiation time, and the color of the solution gradually turned red in the infrared thermal image. The corresponding photothermal temperature curve is shown in Figure 2. Figure 7As shown in (B), after 808 nm laser irradiation for 5 min, the temperatures of Au@Ag nanoparticles, lychee-shaped hollow Au / Ag nanoparticles and Au / Ag@Cu2O nanocomposites increased by 19.2, 30.2 and 43.4, respectively.

[0119] To explain its efficient photothermal conversion, we propose a photothermal conversion mechanism, such as Figure 7 (C), for Au@Ag nanoparticles and lychee-shaped hollow Au / Ag nanoparticles, it is well known that the extinction effect reflects the sum of absorption and scattering. When the incident light irradiates the surface of the nanoparticles, the absorbed light can be quickly converted into heat through a series of physical processes. The scattering or reflection of the incident light on the surface of the solid spherical nanoparticles will lead to a decrease in the absorption of light by the particles. The presence of the cavity in the hollow nanoparticles allows the light to undergo multiple reflections in it, which will increase its total absorption efficiency. And multiple reflections and refractions will also occur at the tip structure outside the particles. Therefore, the multiple interactions between light and the hollow lychee-shaped nanostructures improve the utilization of near-infrared light. For Au / Ag@Cu2O nanocomposites, due to the enhanced local field, the constructed metal semiconductor hybrid can enhance the absorption intensity, and the strong LSPR coupling effect of Cu2O and Au / Ag can also improve the photothermal performance of the nanoparticles, thus showing better photothermal performance than hollow Au / Ag nanoparticles.

[0120] Depend on Figure 7 (D) It can be seen that Au / Ag@Cu2O nanocomposite exhibits the best photothermal performance (η=61.3%), making it a promising candidate material for photothermal sensing due to its excellent photothermal ability. Finally, we conclude that the integration of Au / Ag and Cu2O can not only enhance the SERS effect, but also improve the photothermal conversion efficiency through LSPR coupling.

[0121] Example 3

[0122] A method for preparing an Au / Ag@Cu2O-4-MBA-Van nanocomposite material comprises the following steps:

[0123] 1 mL of 1 mM 4-mercaptobenzoic acid aqueous solution was added to 10 mg of Au / Ag@Cu2O nanocomposite material, and the chelation reaction was carried out by ultrasonication at room temperature for 3 h, centrifuged, and the solid was washed with water twice to obtain an intermediate;

[0124] The intermediate was dispersed in 10 mL of MES buffer at pH 6, and then 10 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride was added, and an activation reaction was carried out at room temperature for 20 min to activate the carboxyl group. Then 5 mg of vancomycin was added, and the grafting reaction was carried out by ultrasound at room temperature for 2 h. Then, 100 μL of ethanolamine was added, and a blocking reaction was carried out at room temperature for 30 min to inactivate the unreacted carboxyl group. The solid was centrifuged, washed 3 times with deionized water, and then stored in 500 μL of PBS buffer.

[0125] Example 4

[0126] An LFA test strip was prepared, which included a sample pad, a conjugation pad, a nitrocellulose membrane (NC membrane), an absorption pad and a plastic support base, wherein a detection line (T line) was provided on the NC membrane, and an Escherichia coli aptamer was coated in the T line of the NC membrane. The prepared NC membrane was dried at 37° C. for 4 h, and the NC membrane was placed on a plastic support base, wherein the NC membrane had two opposite ends, the conjugation pad and the absorption pad were placed and pressed on the two ends of the NC membrane, respectively, the sample pad was pressed on one end of the conjugation pad and the sample pad was away from the absorption pad, and finally the test strips were cut into individual strips for later use.

[0127] A series of concentrations of E. coli were mixed with the SERS nanotag (Au / Ag@Cu2O-4-MBA-Van nanocomposite prepared in Example 3) and added to the sample pad of the LFA test strip. The test results can be judged by naked eyes after 10 minutes. The results are shown in Figure 2. Figure 8 shown.

[0128] The above-mentioned LFA test strip can also set a quality control line on the nitrocellulose membrane. For the convenience of the experiment, no quality control line is set here; the SERS nanotag of the above-mentioned LFA test strip is generally added to the binding pad. For the convenience of the experiment, Escherichia coli and the SERS nanotag are mixed and added to the sample pad here.

[0129] Figure 8 The results of LFA detection using Au / Ag@Cu2O-4-MBA-Van nanocomposites as nanolabels, including the colorimetric photos (A) and photothermal photos (B) of the LFA test strips of E. coli at different concentrations; (C) -8 cfu / mL) of Escherichia coli, (D) is 1589 cm -1 Logarithmic plot of SERS intensity and E. coli concentration.

[0130] Depend on Figure 8 (A) It can be seen that by monitoring the color of the T line with the naked eye, as the concentration of the E. coli solution increases, the color of the T line becomes darker, indicating that more and more nanotags are captured on the T line. Therefore, the visual detection limit is 103 cfu / mL, at this concentration, the color of the test line almost disappears.

[0131] Depend on Figure 8 (B) It can be seen that for photothermal-LFA, at 1.5 W cm -2 After irradiation with a near-infrared 808nm laser for 5 minutes, the thermal image was immediately collected with an infrared camera. When the concentration of E. coli increased, the number of nanoprobes captured by the T line increased, the temperature of the T line increased, and the thermal image gradually changed from blue to red. At the same time, the photothermal signal can be detected in 10 2 Therefore, compared with colorimetric-LFA, photothermal signaling can expand the response range of target analytes.

[0132] Depend on Figure 8 (C) It can be seen that for quantitative SERS-LFA, the molecular SERS signal of the Raman reporter molecule 4-MBA can indirectly reflect the SERS signal of the target bacteria. Figure 8 (D) shows the Au / Ag@Cu2O-4-MBA-Van nanocomposite as a nanotag, and the concentration of 4-MBA adsorbed on it is related to the 1589 cm -1 The corresponding SERS intensity at the same location increases with the increase of E. coli concentration. 1 cfu / mL, the SERS signal still exists. The SERS intensity of 4-MBA is linearly related to the logarithm of the 4-MBA concentration, and the correlation coefficient R 2 It is 0.987, indicating that the nanotag can achieve quantitative SERS detection of the target reporter molecules.

[0133] Example 5

[0134] In order to evaluate the photothermal sterilization ability of the Au / Ag@Cu2O-4-MBA-Van nanocomposite prepared in Example 3 as a nanotag in the near-infrared region, the nanotag was used to inactivate Escherichia coli under the irradiation of 808nm laser. 100μL of nanotags and 500μL of Escherichia coli were placed in a well plate and incubated at 37°C for 30min. After 808nm laser irradiation for 5min, the survival rate of Escherichia coli was detected using the Calcein-AM / PI double staining kit. At the same time, three parallel experiments were performed, including (1) Escherichia coli in the presence or (2) absence of laser irradiation, and (3) Escherichia coli grown only with nanotags. All fluorescence images were acquired using a MicroSpec system. The results are shown in Figure 2. Fig. 9 shown.

[0135] Fig. 9The plasmonic photothermal effect and cytotoxicity results of Au / Ag@Cu2O-4-MBA-Van nanocomposite as nanotag, including live and dead fluorescence images of Escherichia coli with (A) no laser treatment, (B) laser treatment only, (C) nanotag treatment only, and (D) simultaneous treatment of nanotag and near-infrared laser.

[0136] Depend on Fig. 9 It can be seen that: In order to study the plasmonic photothermal effect and cytotoxicity of Au / Ag@Cu2O-4-MBA-Van nanocomposite as a nanotag, the CalceinAM / PI double staining experiment was used to study the inactivation of Escherichia coli by the nanotag under 808nm laser irradiation, which can visually distinguish between live and dead cells. Among them, live E. coli and dead E. coli showed green and red fluorescence, respectively. It can be seen that E. coli still survives regardless of laser treatment or not. Simple laser irradiation cannot effectively inactivate bacteria, which directly confirms the inactivation effect of laser irradiation on bacteria. In addition, when E. coli was treated with nanotags alone, almost no dead bacteria were found, which indirectly indicated that the cytotoxicity of nanotags to E. coli was negligible. However, once E. coli was treated with nanotags under laser irradiation, almost all E. coli were killed. The possible bactericidal mechanism behind this is that after near-infrared laser irradiation, the heat generated by the nanotags can cause membrane damage and denaturation of proteins and enzymes, leading to bacterial death.

[0137] In summary, in order to achieve sensitive and reliable detection and inactivation integration of target bacteria, the present invention constructed a multifunctional Au / Ag@Cu2O-4-MBA-Van nanocomposite material with colorimetric-photothermal-Raman performance characteristics, which can be used as a nanotag for multimodal sensitive detection of bacteria (such as colorimetric LFA, photothermal LFA and SERS LFA) and photothermal inactivation.

[0138] Compared with the traditional LFA, the Au / Ag@Cu2O-4-MBA-Van nanocomposite of the present invention integrates colorimetric, photothermal and SERS modes, which can provide more attractive and sensitive results. And under the irradiation of near-infrared laser, the nanotag effectively killed Escherichia coli within 5 minutes. Therefore, the multimodal lateral flow immunoassay based on Au / Ag@Cu2O nanocomposite can provide a universal and promising sensing platform for ultra-high sensitivity detection of bacteria, and can perform effective photothermal sterilization, which has great potential in the detection and control of bacteria.

[0139] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A lychee-shaped hollow Au / Ag nanoparticle, characterized in that: The nanoparticles include: Au element and Ag element. The surface of the nanoparticles is rough and lychee-shell-shaped, and the interior of the nanoparticles is hollow. Preferably, the particle size of the lychee-shaped hollow Au / Ag nanoparticles is 80-100nm.

2. A method for preparing the lychee-shaped hollow Au / Ag nanoparticles as claimed in claim 1, characterized in that: The method comprises the following steps: mixing a nano-Ag seed solution, an Au source solution, a reducing agent and a surfactant, and reacting the mixture to obtain lychee-shaped hollow Au / Ag nanoparticles; Preferably, the reducing agent is at least one of hydroquinone and hydrazine hydrate; preferably, the surfactant is at least one of polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate; preferably, the Au source is at least one of tetrachloroauric acid, tetrachloroauric acid trihydrate and tetrachloroauric acid tetrahydrate; preferably, the weight ratio of nano-Ag and Au element is 1:1-2; preferably, the weight ratio of nano-Ag, surfactant and reducing agent is 1:50-100:150; preferably, the reaction is carried out at room temperature for 20-40 minutes with stirring at a speed of 800-1000r / min.

3. An Au / Ag@Cu2O nanocomposite material, characterized in that: include: Litchi-shaped hollow Au / Ag nanoparticles and a Cu2O layer coated on the surface of the litchi-shaped hollow Au / Ag nanoparticles, wherein the litchi-shaped hollow Au / Ag nanoparticles are the litchi-shaped hollow Au / Ag nanoparticles as claimed in claim 1; preferably, the thickness of the Cu2O layer is 10-30nm.

4. A method for preparing the Au / Ag@Cu2O nanocomposite material as claimed in claim 3, characterized in that: The method comprises the following steps: mixing lychee-shaped hollow Au / Ag nanoparticles, a surfactant, a copper source, an alkaline substance and a solvent, and then adding a reducing agent to react to obtain an Au / Ag@Cu2O nanocomposite material; Preferably, the solvent is at least one of water and ethanol; preferably, the surfactant is at least one of hexadecyltrimethylammonium bromide and polyvinylpyrrolidone; preferably, the copper source is at least one of copper chloride and copper hydroxide; preferably, the alkaline substance is sodium hydroxide; preferably, the reducing agent is at least one of ascorbic acid and hydrazine hydrate; preferably, the dosage ratio of lychee-shaped hollow Au / Ag nanoparticles and copper source is 1 mg:1.5-2 mmol; preferably, the molar ratio of copper source, surfactant and alkaline substance is 1:2-3:0.2-0.25; preferably, the molar ratio of copper source and reducing agent is 1:4-5; preferably, the reaction is carried out at room temperature for 20-40 min.

5. An Au / Ag@Cu2O-4-MBA-Van nanocomposite material, characterized in that: A 4-mercaptobenzoic acid layer and a vancomycin layer are grafted and coated on the surface of the Au / Ag@Cu2O nanocomposite material in sequence from the inside to the outside, wherein the Au / Ag@Cu2O nanocomposite material is the Au / Ag@Cu2O nanocomposite material as claimed in claim 3.

6. A method for preparing the Au / Ag@Cu2O-4-MBA-Van nanocomposite material as claimed in claim 5, characterized in that: The method comprises the following steps: mixing a 4-mercaptobenzoic acid solution with an Au / Ag@Cu2O nanocomposite material, performing a chelating reaction, and performing solid-liquid separation to obtain an intermediate; mixing a buffer solution in which the intermediate is dispersed with an activator, performing an activation reaction, then adding vancomycin, performing a grafting reaction, then adding a blocking agent, performing a blocking reaction, and performing solid-liquid separation to obtain an Au / Ag@Cu2O-4-MBA-Van nanocomposite material.

7. The method for preparing the Au / Ag@Cu2O-4-MBA-Van nanocomposite material according to claim 6, characterized in that: The solvent of the 4-mercaptobenzoic acid solution is at least one of water and ethanol; preferably, the amount of 4-mercaptobenzoic acid and Au / Ag@Cu2O nanocomposite material is 0.0005-0.0015mmol:10mg; preferably, the chelation reaction is carried out at room temperature for 2-4h; preferably, the buffer is MES buffer with a pH of 4-6; preferably, the activator is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; preferably, the weight ratio of Au / Ag@Cu2O nanocomposite material to the activator is 1: 0.8-1.2; preferably, the activation reaction is carried out at room temperature for 20-30 minutes; preferably, the weight ratio of Au / Ag@Cu2O nanocomposite material to vancomycin is 1:0.4-0.6; preferably, the grafting reaction is carried out at room temperature for 1.5-2.5 hours; preferably, the blocking agent is at least one of ethanolamine and bovine serum albumin; preferably, the amount ratio of Au / Ag@Cu2O nanocomposite material to the blocking agent is 10 mg:0.08-0.12 mL; preferably, the blocking reaction is carried out at room temperature for 20-40 minutes.

8. Use of the Au / Ag@Cu2O-4-MBA-Van nanocomposite material as claimed in claim 5 as a SERS nanotag.

9. An LFA test paper, characterized in that: include: A sample pad, a conjugate pad, a nitrocellulose membrane, an absorption pad and a bottom plate, wherein the conjugate pad contains a SERS nano-tag; Wherein, the SERS nanotag is at least one of the Au / Ag@Cu2O-4-MBA-Van nanocomposite materials as described in claim 5; preferably, a detection line is provided on the nitrocellulose membrane; preferably, a quality control line is provided on the nitrocellulose membrane.

10. An application of the lychee-shaped hollow Au / Ag nanoparticles as claimed in claim 1, the Au / Ag@Cu2O nanocomposite as claimed in claim 3, the Au / Ag@Cu2O-4-MBA-Van nanocomposite as claimed in claim 5, or the LFA test paper as claimed in claim 9 in SERS detection, LFA detection, photothermal detection, and photothermal sterilization; preferably, in SERS detection of bacteria, LFA detection of bacteria, photothermal detection of bacteria, and photothermal sterilization; preferably, the bacteria are at least one of Escherichia coli, Salmonella, and Staphylococcus aureus.